2009
DOI: 10.1002/cncr.24270
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cancer mortality‐to‐incidence ratios to illustrate racial and sex disparities in a high‐risk population

Abstract: BACKGROUND: Comparisons of incidence and mortality rates are the metrics used most commonly to define cancer‐related racial disparities. In the US, and particularly in South Carolina, these largely disfavor African Americans (AAs). Computed from readily available data sources, the mortality‐to‐incidence rate ratio (MIR) provides a population‐based indicator of survival. METHODS: South Carolina Central Cancer Registry incidence data and Vital Registry death data were used to construct MIRs. ArcGIS 9.2 mapping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 30 publications
(38 reference statements)
3
133
0
3
Order By: Relevance
“…AAs also are diagnosed at younger ages, on average and with later-stage disease, have a higher incidence before the recommended screening age of 50 years, and tend to have worse prognoses even after accounting for other factors [2, 3]. These disparities tend to be much larger in South Carolina (SC) than in the US average [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…AAs also are diagnosed at younger ages, on average and with later-stage disease, have a higher incidence before the recommended screening age of 50 years, and tend to have worse prognoses even after accounting for other factors [2, 3]. These disparities tend to be much larger in South Carolina (SC) than in the US average [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Racial differences were recorded in all types of cancer. The biggest racial differences were recorded in breast and prostate cancer (Hébert et al, 2009). The social environment may affect different types of cancer in different ways .…”
Section: Theoretical Aspects Of Cancer Incidencementioning
confidence: 99%
“…Table 4 shows that 13 CNP networks (#1, 4,6,7,11,12,13,16,18,19,21,23,24) reported that their education and information policy activities, often in conjunction with a broader coalition, resulted in decision-makers either changing policies or affecting a change in the policy agenda. Eight CNPs worked on smoke-free policies (#1, 4,7,11,13,16,18,19), three CNPs worked on allocation of funds for tobacco control programs and research (#6, 19, 23), four CNPs educated policymakers on implementing comprehensive tobacco control (#11, 18,19,21), and one CNP (#24) worked on a city ordinance for storefront advertising.…”
Section: Domain 2: Reducing Tobacco Use and Related Diseasesmentioning
confidence: 99%